2009
DOI: 10.5194/acp-9-6705-2009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of particle size on the ice nucleating ability of mineral dusts

Abstract: The recently developed Zurich Ice Nucleation Chamber (ZINC) was used to explore ice nucleation of size-selected mineral dust particles at temperatures between −20 • C and −55 • C. Four different mineral dust species have been tested: montmorillonite, kaolinite, illite and Arizona test dust (ATD). The selected particle diameters are 100 nm, 200 nm, 400 nm and 800 nm. Relative humidities with respect to ice (RH i ) required to activate 1% of the dust particles as ice nuclei (IN) are reported as a function of tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
235
3
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(274 citation statements)
references
References 30 publications
34
235
3
2
Order By: Relevance
“…The role of IN modes upon the estimation of n s was also examined across various temperature ranges. The EDB-based method was used to measure the contact and immersion mode efficiencies of size segregated dry illite NX particles around −30 • C. Immersion freezing results from IMCA-ZINC were compared to previously reported ZINC data (Welti et al, 2009) at temperatures below −31 • C and to PINC data for temperatures below −26 • C. In the present study, we derived ZINC's n s values from the results reported in Welti et al (2009). Specifically, ice formation above 105 % RH w up to the water drop survival line was used to calculate n s based on given illite NX particle sizes.…”
Section: Ice Nucleation Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of IN modes upon the estimation of n s was also examined across various temperature ranges. The EDB-based method was used to measure the contact and immersion mode efficiencies of size segregated dry illite NX particles around −30 • C. Immersion freezing results from IMCA-ZINC were compared to previously reported ZINC data (Welti et al, 2009) at temperatures below −31 • C and to PINC data for temperatures below −26 • C. In the present study, we derived ZINC's n s values from the results reported in Welti et al (2009). Specifically, ice formation above 105 % RH w up to the water drop survival line was used to calculate n s based on given illite NX particle sizes.…”
Section: Ice Nucleation Measurementsmentioning
confidence: 99%
“…In this figure, panels i, ii and iii show T -binned data averaged in the linear space of all 17 instruments, all suspension type measurements, and all measurements that involved dry particles, respectively, while panel iv shows a comparison between suspension and dryparticle measurements. We note that the data from "EDB (contact)" and "ZINC" (Welti et al, 2009) were not used for generating T -binned data since our focus was on immersion mode freezing. We also note that the n s results from nine IN measurement techniques provide n s data at −23 and −24 • C, where we find an abrupt increase in log(n s )/ T and n s deviations.…”
Section: Dry Vs Suspension N S (T ) Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral dust acts as an ice nucleus over a wide range of temperatures and supersaturations over ice, with the most active dusts nucleating ice at approximately 260 K (Welti et al, 2009;Eastwood et al, 2009;Hoose and Möhler, 2012;Murray et al, 2012;YakobiHancock et al, 2013). Using numerical modeling to estimate the climate impact of mineral dust through ice formation requires relations which connect aerosol properties, thermodynamic variables and resulting ice crystal concentrations.…”
Section: Steinke Et Al: Describing Deposition Ice Nucleation By Amentioning
confidence: 99%
“…INAS densities were also derived from ice fractions f ice observed in studies investigating the deposition nucleation mode properties of monodisperse ATD particles (Koehler et al, 2010;Sullivan et al, 2010;Welti et al, 2009) with…”
Section: General Ice Nucleation Active Surface Density Approachmentioning
confidence: 99%